2018
DOI: 10.1200/jco.2018.78.7101
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of 4L Lymph Node Dissection in Left Lung Cancer

Abstract: Station 4L LN involvement is not rare in left lung cancer, and dissection of the 4L LN station seems to be associated with a more favorable prognosis as compared with those who did not undergo this dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 26 publications
5
34
0
Order By: Relevance
“…Because of the deep anatomic location of 4L lymph node, which lies to the left of the left lateral border of the trachea and medial to the ligamentum arteriosum enveloped by aortic arch and left pulmonary artery, 8 dissection of 4L lymph node is technically challenging with high risk of left recurrent laryngeal nerve paralysis 9 . Therefore, some thoracic surgeons chose to neglect 4L LND for left‐sided NSCLC 10,11 . However, recent evidence showed that dissection of 4L lymph node could benefit patients with left‐sided NSCLC, 11–13 arguing for the necessity of 4L LND for left‐sided NSCLC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the deep anatomic location of 4L lymph node, which lies to the left of the left lateral border of the trachea and medial to the ligamentum arteriosum enveloped by aortic arch and left pulmonary artery, 8 dissection of 4L lymph node is technically challenging with high risk of left recurrent laryngeal nerve paralysis 9 . Therefore, some thoracic surgeons chose to neglect 4L LND for left‐sided NSCLC 10,11 . However, recent evidence showed that dissection of 4L lymph node could benefit patients with left‐sided NSCLC, 11–13 arguing for the necessity of 4L LND for left‐sided NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some thoracic surgeons chose to neglect 4L LND for left‐sided NSCLC 10,11 . However, recent evidence showed that dissection of 4L lymph node could benefit patients with left‐sided NSCLC, 11–13 arguing for the necessity of 4L LND for left‐sided NSCLC. However, previous evidence for the benefit of 4L LND for left‐sided NSCLC is limited due to the small sample size of individual study and retrospective study design, 11–13 and as a result, meta‐analysis pooling of all available relevant evidence together is needed for robust validity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-small cell lung cancer (NSCLC) tumor cells usually appear in regional lymph nodes before they are detected in distant organs. The presence of lung cancer cells in lymph nodes is a major indicator in the staging of NSCLC and is associated with poor prognosis 4 , 5 . Tumor lymphangiogenesis is strongly correlated with increased incidence of lymph node metastasis and decreased overall survival in several types of human cancers 6 8 and experimental cancer models 9 11 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the metastasis of other lymph nodes may affect the 4L lymph node metastasis and the tumor size. However, by a multivariate analysis, they all found positive left hilar lymph node result, which might be one of the independent risk factor for 4L lymphatic metastasis (22)(23)(24). This is consistent with our conclusion, which provides thoracic surgeons an indication: The intraoperative rapid frozen section pathological examination of station 10L lymph node may be a good choice.…”
Section: Discussionmentioning
confidence: 99%